TRANSFORMASI UMKM DIGITAL BERBASIS POTENSI LOKAL - Enny Diah Astuti; Tarto Tarto; Rahayu Tri Utami; Venny Oktaviany (JURNAL LENTERA BISNIS, 2025)
One important area of the Indonesian economy is MSMEs (Micro, Small, and Medium Enterprises). The use of technology in marketing and transactions is only one aspect of MSMEs' digitization; other aspects include incorporating technology into production, distribution, financial administration, and customer service. But not everyone benefits equally from this shift, which is frequently impeded by a lack of funding, poor levels of digital literacy, and restricted access to technology. This study examined how MSME communities in Pengalengan, West Java, are driving the regional economy through economic empowerment initiatives. employing a qualitative approach model that offers an alternative viewpoint for comprehending the issues identified in the study in order to conduct a more thorough and in-depth analysis. MSMEs may boost efficiency and market access while also generating sustainable added value by leveraging digital technology to enhance local potential. An inclusive digital ecosystem that is sensitive to local dynamics and can support the transformation of Digital MSMEs based on local potential requires collaboration between MSME players, the government, academia, and the business sector to accomplish this change.